”Green technologies” to strengthen the state’s energy stability - Melnychenko, V.D.; Pavliukh, L.I. (Problems of Environmental Biotechnology, 2023)
Ukraine is still dependent on imported energy resources, such as natural gas. Biogas production from organic waste can reduce this dependence, contributing to greater energy stability and diversification.